O caráter doutrinário de Universidades Corporativas - Brauer, Marcus (2004)
This research had the objective to verify if the Corporative Universities have a doctrinal character and why. In order to make the identification and analysis possible, field and bibliographic researches have been used. The bibliographical survey allowed to conclude that university is not the adequate and correct term to identify the Corporative 'University', as an university does not only concern teaching. Regarding research, the investigation seeks the truth, what rarely occurs in Corporate Universities. Besides this, the bibliographical survey furnished information about organizational control and indoctrination that are important to the analysis of the Corporative Universities. While the market needs more critical, creative and enterprising individuals, the Corporative Universities limit the freedom of the thought. The field research is based on the studies of Reboul (1980) and Snook (1974), providing data that made the identification of politics and practices of the researched Corporate University possible, giving them doctrinal characteristics, which are opposed to those of education, but in a reduced degree, as compared with the respondent of the research. This circumstance harmed in a certain way initial supposition of the study, but at its end roused other suppositions as well.